Design and evaluation of a research-educational test bench applied to rotor dynamics studies - De Medeiros, E. C. [UNESP]; Mendonça, W.R. De P.; De Barros, E.; Mathias, M. H. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
The rotor dynamics study is critical in the design of rotating machinery. The dynamic modeling of rotors aims to estimate the operating condition of rotating machinery through the evaluation of parameters related to the critical velocity and responses to unbalance. The application of small-scale test bench and the development of dedicated experimental procedures are important for the grounding of complex rotating high power machines behavior phenomena. The experimental evaluation is an important validation of theoretical models, such as those obtained by analytical and numerical models. This work aims the description of an experimental test bench, and later were the object of study to be modeled in several conditions: using analytical, numerical and experimental methods. In the end, with all these results, there is a comparative assessment of the modeling and validation of equipment.
Keywords: Rotating Machinery; Rotor Dynamics; Test bench